Kesulitan Konseptual Siswa dalam Transisi ke Akuntansi Terkomputerisasi pada Pembelajaran MYOB Accounting di SMK Swasta Lamaholot Larantuka - Maria Fatima Bongi Beribe; Silvester Ratu Sogen (Journal of Creative Student Research, 2026)
This study aims to analyze the implementation of MYOB Accounting learning and identify students conceptual difficulties in the transition process from manual accounting to computerized accounting for class XI Accounting and Institutional Finance (AKL) students at SMK Swasta Lamaholot Larantuka. This study uses a qualitative approach with an exploratory descriptive method. Data were obtained through interviews, observations, and documentation of accounting teachers and class XI AKL students. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. Data validity was carried out through source triangulation and technical triangulation. The results of the study indicate that MYOB Accounting learning helps students understand the accounting cycle more systematically, from recording to preparing financial reports. However, students still experience conceptual difficulties in mapping manual accounts into the MYOB system, understanding English terms, and establishing transaction input flows in the application. Teachers overcome these difficulties by reinforcing basic accounting concepts, intensive mentoring, and integrating manual recording with digital practices as well as in understanding English terms used in the application. This study concludes that learning MYOB Accounting can improve students’ understanding of accounting if accompanied by structured conceptual guidance in the transition process towards computerized accounting.